Analysis of Learning Motivation on Critical Thinking and Collaboration Skills of High School Students in Science Learning - Ayu Rahmi; Muttakin Muttakin; Sri Setiawaty; Sirry Alvina; Eka Juliana; Zainul Mujtahid (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
Science learning plays a crucial role in developing students' high order thinking skills (HOTS), particularly critical thinking and collaboration. In chemistry learning, which is part of science, the content tends to be abstract and conceptual, learning motivation is an internal factor that determines students' active involvement in scientific thinking and group collaboration. This study aims to analyze the influence of learning motivation on students' critical thinking and collaboration skills (CTCS) in chemistry learning. The study used a quantitative approach with an ex post facto survey method. The subjects of this study were eleventh-grade students from three secondary education units in Lhoksukon District, namely SMAN 1 Lhoksukon, SMAN 3 Putra Bangsa, and MAN 2 North Aceh, with a sample size of 305 students selected through purposive sampling technique. Data collection was conducted using a closed-ended Likert-scale questionnaire that was analyzed descriptively. The results of this study indicate a significant relationship between learning motivation and students' CTCS. Data analysis shows that the achievement of collaboration skills is at a higher level than critical thinking skills (CTS). The percentage of learning motivation's influence on CTS is in the range of 82–85%, while on collaboration skills it is in the range of 84–87%. This finding confirms that learning motivation plays a key factor in supporting the development of critical and collaborative thinking skills in chemistry learning. Therefore, chemistry learning needs to be strategically designed to foster learning motivation in order to be able to improve the quality of the learning process and outcomes in a sustainable manner